Knowledge Management: Tinjauan Pemberdayaan pada Perusahaan Umumnya - Darudiato, Suparto; Suryadi, Lince (Bina Nusantara University, 2013)
Knowledge management is not a new concept but its use in the firm still holds a very important role. This paper aims to further introduce the concept of knowledge management, which in its implementation has so many benefits that can be gained, barriers that can interfere, and things that must be considered. From thebenefits and barriers of knowledge management?s implementation, we can analyze the future of knowledge management use. To support this paper, data and information are searched through some books, journals, and articles that related with topic. The result of this paper is a comprehension about knowledge management concept and its implementation to firm.